Implementasi Green Hotel Dalam Bentuk Green Action di Casa Kandara Hotel Waingapu Sumba Timur - Prayogi, Putu Agus; Susila, I Made Gede Darma; Wisnawa, I Made Bayu (JURNAL BISNIS HOSPITALITI, 2024)
In realizing sustainable tourism, the implementation of green action is needed as a concrete form of action that can be taken. Casa Kandara Hotel is one of the hotel accommodations that implements green action as a form of concern for the surrounding environment. The purpose of this study was to determine the extent of the implementation of green hotels in the form of green action at Casa Kandara Hotel Waingapu East Sumba. This research method uses a qualitative approach with observation and interview data collection techniques. And analyzed using qualitative descriptive analysis with the approach of the concept of accommodation, green hotel and green action. The results of this study indicate that there are concrete green actions that have been carried out by Casa Kandara Hotel. Green actions in question such as electrical energy efficiency, water energy efficiency, utilization of local products and environmentally friendly waste treatment. It is hoped that there will be a joint commitment from both the management and management of accommodation as well as the role of the government in implementing environmentally friendly green action. This is so that all accommodations in Waingapu can implement environmentally friendly concepts in their respective accommodations.